Global economic crisis: Is Georgia at risk? - Maka Bughulashvili (IBSU Scientific Journal (IBSUSJ), 2009)
Most of countries have been badly affected by the tremendous global financial crisis and economic downturn happening recently. It is really difficult to predict the timing and magnitude of events caused by the global economic crises, the effects of the crisis vary from country to country. It has become a serious problem not only for those countries which belong to the world of unprecedented financial globalization, where the financial sector plays a historically large role in economic activity, but it is also an imported crisis (G20 Financial Ministers' Meeting, November,2008) for low-income countries (LICs) as well. Although Georgia's economy is quite small, it is not isolated from the recession dilemma facing the world economy. In this article I look at how the global financial crisis may affect the Georgian economic development, export-import structure, investment flows and those sectors of Georgian economy which are regarded as having suffered the most because of the financial crisis spreading around the globe. This paper is kind of attempt to find out what are the optimal measures to recover from the post-August war condition and how to avoid direct influence of the global crisis on Georgian economy
Keywords: 330